Perancangan Disaster Recovery Planning Pada Aplikasi Cerdik Menggunakan AWS Elastic DR - Firdaus Putra Aditya, Wigananda; Ismail, Jefri Abdurrozak; Sari, Anggraini Puspita (Journal of Information System and Technology (JOINT), 2025)
Tracer Study is a survey method to track alumni career trajectories, offering insights into workforce transition, competency application, and institutional connections. Universitas Dinamika (Undika) conducts this survey through a web-based application, Tracer Study Dinamika (Cerdik). However, its manual data backup process poses risks of data loss and service disruption. This study aims to design a Disaster Recovery Plan (DRP) using the Cold Site Disaster Recovery (Cold DR) approach for enhanced efficiency and data protection. A qualitative method involving interviews, observations, and literature reviews was employed. The resulting AWS Cloud-based DR architecture utilizes Elastic Disaster Recovery for automated data replication, ensuring up-to-date data and simplified recovery during system failures. With secure communication via VPN, Web Application Firewall (WAF) protection, and DR simulation for defining Recovery Time Objective (RTO) and Recovery Point Objective (RPO), this cost-effective solution suits applications with longer recovery tolerance.